2017
DOI: 10.3390/rs9020124
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon Stock and Particle Size Fractions in the Central Amazon Predicted from Remotely Sensed Relief, Multispectral and Radar Data

Abstract: Soils from the remote areas of the Amazon Rainforest in Brazil are poorly mapped due to the presence of dense forest and lack of access routes. The use of covariates derived from multispectral and radar remote sensors allows mapping large areas and has the potential to improve the accuracy of soil attribute maps. The objectives of this study were to: (a) evaluate the addition of relief, and vegetation covariates derived from multispectral images with distinct spatial and spectral resolutions (Landsat 8 and Rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…; Ceddia et al. ). This suggests that Landsat images could be used as an environmental layer in species distribution modelling and other applications that require in situ data to be interpolated across large areas.…”
Section: Introductionmentioning
confidence: 98%
“…; Ceddia et al. ). This suggests that Landsat images could be used as an environmental layer in species distribution modelling and other applications that require in situ data to be interpolated across large areas.…”
Section: Introductionmentioning
confidence: 98%
“…The terrain controls the flow of solute, water, and sediment, which in turn affects the development of soil and the spatial distribution of soil properties [63]. Although terrain factors have a significant correlation with SOC content [64], the prediction ability of the model can be significantly improved by adding vegetation index and backscatter coefficient compared with those using only terrain variables [65]. On the one hand, the vegetation features have enough heterogeneity, and there is a strong interaction between vegetation features and soil properties [66].…”
Section: Variable Importancementioning
confidence: 99%
“…Our results not only indicate the importance of remote sensing data to predict STN but also emphasize the need to incorporate SAR images. Radar can provide spectral information beyond vegetation cover and soil surface [12], and backscatter signals from SAR images are used to retrieve target properties, such as forest above-ground biomass, soil texture, soil moisture, and salinity. Many studies have shown that information from SAR data, such as the backscatter coefficient, can detect vegetation [64] and soil moisture [65].…”
Section: Importance Of Predictor Variablesmentioning
confidence: 99%
“…For example, Bartsch et al [11] explored the feasibility of C-band ENVISAT ASAR data in soil organic carbon (SOC) mapping and found that the SOC in the study area can be quantified by SAR images. Ceddia et al [12] used optical and L-band ALOS PALSAR data to conduct SOC prediction studies in central Amazon, and found that the backscattering coefficient of SAR data can improve the prediction accuracy. A similar study was also reported by Ma et al [13], who used SAR (Sentinel-1) and optical (Landsat 7) images to map soil properties in eastern China.…”
Section: Introductionmentioning
confidence: 99%